Sensitivity to light sterile neutrino mixing parameters with KM3NeT/ORCA - Aiello, S.; Albert, A.; Alshamsi, M.; Alves Garre, S.; Aly, Z.; Ambrosone, A.; Ameli, F.; Andre, M.; Androulakis, G.; Anghinolfi, M.; Anguita, M.; Anton, G.; et al. (Journal of High Energy Physics, 2021)
International audience KM3NeT/ORCA is a next-generation neutrino telescope optimised for atmospheric neutrino oscillations studies. In this paper, the sensitivity of ORCA to the presence of a light sterile neutrino in a 3+1 model is presented. After three years of data taking, ORCA will be able to probe the active-sterile mixing angles θ$_{14}$, θ$_{24}$, θ$_{34}$ and the effective angle θ$_{μe}$, over a broad range of mass squared difference $ Δ {m}_{41}^2 $ ∼ [10$^{−5}$, 10] eV$^{2}$, allowing to test the eV-mass sterile neutrino hypothesis as the origin of short baseline anomalies, as well as probing the hypothesis of a very light sterile neutrino, not yet constrained by cosmology. ORCA will be able to explore a relevant fraction of the parameter space not yet reached by present measurements.[graphic not available: see fulltext]